2020
DOI: 10.3390/educsci10090229
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Academic Self-Efficacy Beliefs of Omani School and University Students

Abstract: The present study examined the predictive role of students’ perceptions of parenting styles on their academic efficacy beliefs. This relationship was examined using two large sets of national data that were collected from school and university students to see how the relationship between parenting styles and academic efficacy beliefs may or may not vary across life stages. The sample included 1431 school students and 1119 university students cross the Sultanate of Oman. The participants responded to the Arabic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Arrived at a similar finding, asserting that parental style is a significant predictor of student self-efficacy growth. Similarly, he asserts that authoritative parenting is a key predictor of self-efficacy in the positive direction ( Lau, 2013 ; Wolters and Benzon, 2013 ; McCardle and Hadwin, 2015 ; Aldhafri et al, 2020 ; Khazaie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arrived at a similar finding, asserting that parental style is a significant predictor of student self-efficacy growth. Similarly, he asserts that authoritative parenting is a key predictor of self-efficacy in the positive direction ( Lau, 2013 ; Wolters and Benzon, 2013 ; McCardle and Hadwin, 2015 ; Aldhafri et al, 2020 ; Khazaie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…learning and performance-avoidance orientations. Nevertheless, Aldhafri, et al (2020) found that the effects of parenting styles on students' self-efficacy beliefs declined as the children grew up.…”
Section: Introductionmentioning
confidence: 94%
“…The impact of cultural norms on parenting styles and practices is further underscored by studies (Aghayeeabianeh & Talebi, 2020;Aldhafri et al, 2020;Curelaru et al, 2020) which highlight the effects of parenting styles on students' self-efficacy beliefs, the influence of parenting styles on the strength of the influence of children on parents, and the statistical significance of parenting styles in determining the influence of children on parents, respectively. These references collectively emphasize the need to consider cultural beliefs in understanding the development and impact of parenting styles.…”
Section: Cultural Beliefs and Parenting Practicesmentioning
confidence: 99%